PERANAN EKOLOGIS SHIPWRECK ATAU EXPOSED SHIPWRECK SEBAGAI MEDIA HIDUP KARANG DI PULAU BAWEAN DALAM UPAYA PERLINDUNGAN, PENGEMBANGAN DAN PEMANFAATAN SHIPWRECK ATAU EXPOSED SHIPWRECK - Setyorini, Heny Budi; Priswanto, Hery; Ramadhan, Ahmad Surya (Berkala Arkeologi, 2018)
Abstract Metal salvage and theft activities have eliminated most shipwrecks at Nusa Island, and exposed shipwrecks in Gosong Gili, Bawean Island. In order to give recommendations for its conservation efforts, this study aims to identify the remaining shipwrecks or exposed shipwrecks at Nusa Island and Gosong Gili, and the types of corals and fishes in it. This study aims to prove that shipwrecks or exposed shipwrecks is not only having historical and economical value, but also ecological value for the survival of coral reef ecosystem. This is a descriptive-explorative research, data were gathered by underwater survey using GPS Map Sounder, and SCUBA diving. Shipwrecks at Nusa Island is only 30% left in fragmented form of mast, machine, boiler, propeller, ivory vessel, and bricks in the bow area. While the exposed shipwrecks at Gosong Gili is only 20% left in fragmented form boilers, machine, and ivory vessel that might be a cultural heritage according to the UU RI Number 11 of 2010 on Cultural Heritage. At Nusa Island, the corals are consisted of Poritidae and Acroporidae families, and various species reef fishes. While at Gosong Gili, there are more coral families including Merulinidae, Poritidae and Acroporidae, but their reef fishes species are fewer than Nusa island.